Cleaning and characterization of objects of cultural value by laser ablation - Bilmes, Gabriel Mario (2005)
Surface ablation with nanosecond laser pulses was applied to preservation, cleaning and compositional identification of objects of cultural value. On one hand, treatments of fabrics, coins, bones, and other archeological objects are shown, as well as applications to the preservation of covers, front of books and old manuscripts made in rag paper. Damage fluence thresholds for 17 different XIXth century types of papers, made by processing textiles, were determined. On the other hand, we use the spectroscopic analysis of the plasma generated as a result of laser ablation (LIBS- laser Induced Breakdown Spectroscopy-) for the determination of the elementary composition of unique pieces in anthropology and archaeology. In particular, we show applications to the identification of trace elements in Hominide teeth, of interest concerning the analysis of eating habits. We also apply LIBS to the determination of the composition of acheological objects belonging to different pre Columbian cultures.